Modelo de negócio inovador com foco na produção deconteúdo: estudo de caso de um canal no youtube - Michel Conceição de Souza (2017)
The social platforms allowed new interactions between users through the use of the internet, one of XXI century's most important technological innovations. By the use of the world wide web, people started to issue their opinions and established conections with colective purpose concerning a great variety of subjects, creating space for newmarket segments to emerge. From this context, this study aims to comprehend the job of the content creators making it possible to develop a business based on the production of content for YouTube. For this, the research was conducted based on a hybrid methodology with focus on the analysis of content and a case study, making it a research that is empirical, descriptive and exploratory. Thus, elements of variousmethodological approaches were used, such as data collect, half structured interviews, bibliographical and documental research and a field study. As a research source for the case study, there was the youtuber Marco Tulio, responsible for the channel AuthenticGames (one of the 10 biggest brazilian channels with approximately 11 millions subscribers). It was conducted aiming to comprehend his trajectory since the start of the profissionalization of his job until the development of the business units of this venture. As a result of the research, the business model of the company AuthenticGames Canal and Producoes Ltda. since it's foundation were described. Also, different stages characterized by a centralizing model were identified, with it being a model formed by teams and models of different business units. With this dissertation, it is expected that the research contributes to the reflection about new business models on the internet and the identification of maket opportunities based on the production of videos for the YouTube platform